Multiphoton Fabrication of Proteinaceous Nanocomposite Microstructures with Photothermal Activity in the Infrared. Issue 13 (4th May 2020) - Zeynali, Amirbahador; Marini, Mario; Chirico, Giuseppe; Bouzin, Margaux; Borzenkov, Mykola; Sironi, Laura; D'Alfonso, Laura; Pallavicini, Piersandro; Cassina, Valeria; Mantegazza, Francesco; Granucci, Francesca; Marongiu, Laura; et al.
Abstract: Two‐photon laser writing is used here to fabricate 3D proteinaceous microstructures with photothermal functionality in the near‐infrared spectral region and tunable elasticity. The photo‐cross‐linking is initiated in bovine serum albumin (BSA) by rose bengal or methylene blue and the photo‐thermal effect arises from gold non‐spherically symmetric nanoparticles dispersed in the ink. Massive energy transfer of the plasmonic resonances of the gold nanoparticles to methylene blue prevents effective photo‐crosslinking of BSA. However, stable microstructures with photo‐thermal functionality can be fabricated in the rose bengal proteinaceous inks. On these microstructures, with a gold atom concentration as low as 1% w/w, a highly localized temperature increase can be quickly (≅1 s) reached and maintained under continuous wave laser irradiation at 800 nm. The photothermal efficiency under continuous wave laser irradiation depends on the thickness of the microstructure and can reach 12.2 ± 0.4 °C W −1 These proteinaceous microstructures represent therefore a promising platform for future applications in the fields like physical stimulation of cells for regenerative nanomedicine. Abstract : Two‐photon laser writing is used to fabricate microstructures of BSA protein with a marked photothermal efficiency due to gold non‐spherically symmetric nanoparticles dispersed in the ink. These microstructures show highly localized and fast (ca. 1 s) temperature increase under continuous wave laser irradiation at 800 nm. The photothermal efficiency can reach 12.2 ± 0.4 °C W −1 .